2022
DOI: 10.1007/s11846-022-00529-5
|View full text |Cite
|
Sign up to set email alerts
|

Bank regulation, ownership and risk taking behavior in the MENA region: policy implications for banks in emerging economies

Abstract: This paper investigates the impact of bank regulation and ownership on the risk-taking behavior of financial institutions in the MENA region. We test the hypothesis that the effect of regulation on bank risk depends on the type of ownership structure. The public and private views of bank regulation are used to explain the relationship between regulatory measures and bank risk. We find that the official supervisory index exerts a positively associated with bank credit risk which is in line with ‘private interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 64 publications
5
15
0
Order By: Relevance
“…The banks’ financial stability issue during the COVID-19 pandemic also attracted growing interest among the academic community. Extant research “supports the notion that during the financial crisis, capital responses to the risk-taking behavior of banks are not similar to the normal economic conditions” (Mateev et al 2022a , b , c , p. 2). Moudud-Ul-Huq ( 2021 ) finds “that higher capital promotes banks’ financial stability by lessening the risk, and higher risk impedes capital growth.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 95%
See 1 more Smart Citation
“…The banks’ financial stability issue during the COVID-19 pandemic also attracted growing interest among the academic community. Extant research “supports the notion that during the financial crisis, capital responses to the risk-taking behavior of banks are not similar to the normal economic conditions” (Mateev et al 2022a , b , c , p. 2). Moudud-Ul-Huq ( 2021 ) finds “that higher capital promotes banks’ financial stability by lessening the risk, and higher risk impedes capital growth.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 95%
“…The dependent variable, Prof it is a measure of financial performance (profitability) of bank i in year t ; Effic it variable represents DEA efficiency scores, and Compet it is a measure of banking market competition (the Lerner index); X it is a vector of bank-specific and country-level variables that are known to explain banks’ performance; ϑ 1 to ϑ 4 are the regression coefficients, and ε it is the error term in the model. Following Mateev et al ( 2022b ) approach, we introduce “a vector of dummy variables ( D t ) that includes an ISLAMIC dummy variable that equals 1 if a bank is an Islamic banking institution and 0 otherwise, and a CRISIS time dummy (COVID-19) that takes the value of 1 for the year 2020, and 0 otherwise.We also control for the country fixed effects in each model” (p. 11). Next, we examine the effect of efficiency on bank performance when interacting with the crisis dummy variable.…”
Section: Methodsmentioning
confidence: 99%
“…This risk management has become the main purpose of modern banking. Research has found that increased market discipline and better quality supervision lower risk levels of banks (Mateev et al, 2022). Empirical evidence has shown that this supervision lowers bank risks (Berger and Demirguc-Kunt, 2021).…”
Section: Background Literaturementioning
confidence: 99%
“…This risk management has become the main purpose of modern banking. Research has found that increased market discipline and better quality supervision lower risk levels of banks (Mateev et al. , 2022).…”
Section: Background Literaturementioning
confidence: 99%
“…The evaluation of the banking sector's return to scale (RTS) toward presenting the return to scale (IRS) and steady return to scale, however, is the key topic in the literature (CRS Despite Islamic banking have significantly grown worldwide, few studies have been given to the financial and operational performance. Specific research to evaluate banking efficiency has become crucial since the 1990s (Mateev et al, 2022). It is useful to managers, stakeholders, policy-makers, and regulators, as well as researchers.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%